2015
DOI: 10.1002/ceat.201400732
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Dissolution Kinetics of A and B Polymorphs of L‐Histidine

Abstract: The growth rate of the stable polymorph A and the dissolution rate of the unstable polymorph B of L-histidine (L-his) in aqueous solution were experimentally determined at varying temperatures. The growth and dissolution kinetics were measured by means of desupersaturation and deundersaturation techniques, respectively. Both the growth and dissolution rates increase with higher temperature. At all temperatures studied, the dissolution rate of form B is faster than the growth rate of form A, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
“…Pure crystals of form A of L ‐his were produced from aqueous solution crystallization by cooling operation at 25 °C as described in previous works , , , . A saturated aqueous solution of L ‐his at 45 °C was prepared at 50 °C and then the solution was cooled rapidly to 10 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the B polymorph of L-his is a plate crystal [5], a 2D growth (m = 2) can be assumed. Because the growth of the L-his crystal is controlled by surface integration process [18], b = 1. For the polynuclear nucleation mechanism, the pre-exponential factor in Eq.…”
Section: Theorymentioning
confidence: 99%
“…The solubility data for water‐acetone, water‐ethanol, and water‐propanol have been reported . The data include the solubility as a function of temperature because the solubility of L ‐his increases with temperature . There are reports of the dissolution rate of form B and the growth rate of form A of L ‐his in aqueous solution , and the nucleation and growth mechanisms of form B of L ‐his in the water‐ethanol system .…”
Section: Introductionmentioning
confidence: 99%